2021
DOI: 10.1007/s00330-021-08297-8
|View full text |Cite
|
Sign up to set email alerts
|

Predictive value of gadoxetic acid–enhanced MRI for posthepatectomy liver failure: a systematic review

Abstract: Objectives Effective and non-invasive biomarkers to predict and avoid posthepatectomy liver failure (PHLF) are urgently needed. This systematic review aims to evaluate the efficacy of gadoxetic acid–enhanced MRI-derived parameters as an imaging biomarker in preoperative prediction of PHLF. Methods A systematic literature search was performed in the databases of PubMed/Medline, Web of Science, Embase, and Cochrane Library up to 11 December 2020. Studies eva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 43 publications
0
17
0
Order By: Relevance
“…14 During the last decade, gadoxetic acid-enhanced MRI has been increasingly used for quantitative evaluation of liver function. 13,15 Previous studies have shown that parameters derived from gadoxetic acidenhanced MRI have a good correlation with the retention rate of ICG at 15 min (ICG-R15), Child-Pugh score and the Model for End-Stage Liver Disease score, 12,16,17 making it a promising tool to provide more accurate pre-operative assessment for patients with liver tumors estimating both morphological, volumetric and functional capacity. 15 Compared with the ICG test and HBS, the efficacy and consistency of gadoxetic acid-enhanced MRI remains unclear.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…14 During the last decade, gadoxetic acid-enhanced MRI has been increasingly used for quantitative evaluation of liver function. 13,15 Previous studies have shown that parameters derived from gadoxetic acidenhanced MRI have a good correlation with the retention rate of ICG at 15 min (ICG-R15), Child-Pugh score and the Model for End-Stage Liver Disease score, 12,16,17 making it a promising tool to provide more accurate pre-operative assessment for patients with liver tumors estimating both morphological, volumetric and functional capacity. 15 Compared with the ICG test and HBS, the efficacy and consistency of gadoxetic acid-enhanced MRI remains unclear.…”
Section: Discussionmentioning
confidence: 99%
“…13,15 Previous studies have shown that parameters derived from gadoxetic acidenhanced MRI have a good correlation with the retention rate of ICG at 15 min (ICG-R15), Child-Pugh score and the Model for End-Stage Liver Disease score, 12,16,17 making it a promising tool to provide more accurate pre-operative assessment for patients with liver tumors estimating both morphological, volumetric and functional capacity. 15 Compared with the ICG test and HBS, the efficacy and consistency of gadoxetic acid-enhanced MRI remains unclear. We therefore designed a prospective pilot study to explore gadoxetic acid-enhanced MRI, along with ICG-R15 and HBS to depict the dynamic changes of the liver function and volume after hepatectomy in patients with colorectal liver metastases (CRLM), in which HBS results were adopted as the reference for assessment of liver function.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Signal intensity-based parameters, including the relative liver enhancement, hepatic uptake index, 169 and liver imaging score, 170 are commonly used to evaluate liver function, and these EOB-MRIderived parameters are effective for the preoperative prediction of PHLF. 61,[171][172][173][174][175] The advantages of EOB-MRI include high spatial resolution and combined anatomical and functional assessment, which enable the evaluation of regional liver function and diagnosis of hepatic lesions prior to liver resection. Moreover, it is reasonable to incorporate the FLR volume for precise estimation of postoperative residual function.…”
Section: Gd-eob-dtpa-enhanced Mrimentioning
confidence: 99%
“…For those patients who are not eligible for surgery, a majority of them are due to the limited future liver remnant (FLR), which is the remaining part of the liver after liver resection, and it serves as a key determinant for extended liver resection ( 3 ). FLR has to be sufficient to maintain normal physiologic function after liver resection, otherwise a lethal complication, post-hepatectomy liver failure will occur ( 4 ). To prevent the occurrence of liver failure after liver resection, the FLR volume limit should be > 20% of the total liver in a normal liver, > 30% in the abnormal liver (such as steatosis or post-chemotherapy), and at least 40% in the cirrhotic liver ( 5 ).…”
Section: Introductionmentioning
confidence: 99%